Reinterpreting The Concept of Nusyuz From The Perspective of Islamic Family Law Hermeneutics - Ubaidillah, Ubaidillah; Khaliq, Restu (TATHO: International Journal of Islamic Thought and Sciences, 2025)
The concept of nusyuz in classical fiqh perspectives is often interpreted as a form of wife's defiance against her husband. This interpretation not only reflects the dominant patriarchal view of the past, but also has a significant impact on the formation of family law norms in various modern Muslim societies today. The purpose of this research seeks to reinterpret the concept of nusyuz in the construction of modern society. This qualitative research in the form of a literature study uses a descriptive-analytical approach. The research data used scientific literature related to the reinterpretation of the concept of nusyuz. Hermeneutic theory is used as the basis for perspective. Data were obtained using documentation techniques. Data analysis uses data reduction, presentation, and verification. The results concluded that in a hermeneutic perspective, the condition of the increasing role of women in the public sphere in the construction of modern society has led to changes in family structure, so it is important to reinterpret the concept of nusyuz to be more relevant to the needs of the times and in line with the principles of universal justice promoted by Islamic law. This research contributes to the importance of a contextual understanding of the concept of nusyuz to not only be understood from the normative side, but also from a socio-historical perspective